Philo of Alexandria and the Epistle to the Hebrews on the Concept of the Spiritualization of the Cult - Botica, Aurelian (Perichoresis, 2023)
The Epistle to the Hebrews contains one of the most unique Greek lexicology and syntax of all the New Testament writings. Behind syntax, however, there lies a very profound theological vision on topics such as Christ, Temple, holiness, perseverance and salvation. Studying Hebrews against the background of Graeco-Roman culture, the source that most contemporary scholars mention as being closest to the world of Hebrews in this context is Philo of Alexandria. Not only on philological grounds, but also in matters of methods of interpreting the Old Testament cult and in theology, Hebrews and Philo share a very common background. Analyzing the Epistle to the Hebrews comparatively, we are bound to ask whether or not comparsions such as these are warranted. In the following study we will state the state of the problem and then will examine the two sources that seem to have served as a source of inspiration for the author of Hebrews: the Old Testament and Philo of Alexandria. We will focus exclusively on the issues of the method of allegory and the spiritualization/reinterpretation of Old Testament cultic entities, since both Philo and Hebrews are characterized by these concerns. In essence, we will want to know who or what served as the most plausible source of inspiration for the author of Hebrews in the particular area of the reinterpretation of the Old Testament cult.